Beef and dairy value chains in Senegal: Problems and Opportunities - Chan, Derek; Houessionon, Prosper; Sow, Fafa; Perin, Lucie; Krendelsberger, Alexandra; Seck, Ibrahima; Wane, Abdrahmane; Whitbread, Anthony M.; Worou, Nadine (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Livestock production, especially pastoralism, is a vital part of the Senegalese economy. A large variety of production methods have been observed: from producing milk for household consumption, to collection and transformation by cooperatives to distribute the milk nationwide. The most significant problems faced are increased competition for fewer resources (namely pasture biomass and water) which, compounded with high feed prices and tight margins, contributes to conflict. There are opportunities to improve the marketability of dairy products and milk and beef productivity by improving connections to the market, testing different stabling and feed practices, adapting climate information services to producers’ needs, identifying and rehabilitating transhumance corridors, improving accessibility to feed, and introducing better and more veterinary checks.